Constructing a Labour Gospel: Labour and Religion in Early 20th-century Ontario - Turkstra, Melissa (Labour/Le Travail)

(untitled) (Canadian Committee on Labour History, 2006)
This paper considers the presence of Christianity in the labour movement in early 20th-century Ontario. During this period labour leaders were unquestionably disillusioned with the established churches and did not hesitate to criticize clergymen for their indifference and hostility to labour's cause. This disillusionment did not mean, however, that organized labour abandoned religion. Both moderate reformist and radical labour leaders articulated a non-sectarian, activist Christianity that helped them frame the issues they were concerned about. Alliances also developed between the churches and labour bodies at the national level and labour-friendly clergy and a small group of labour leaders in industrial centres in southern Ontario.